A Reactive Oxygen Species Scavenging and O2 Generating Injectable Hydrogel for Myocardial Infarction Treatment In vivo. Issue 48 (9th November 2020) - Ding, Jie; Yao, Yuejun; Li, Jiawei; Duan, Yiyuan; Nakkala, Jayachandra Reddy; Feng, Xue; Cao, Wangbei; Wang, Yingchao; Hong, Liangjie; Shen, Liyin; Mao, Zhengwei; Zhu, Yang; et al.
Abstract: The excessive reactive oxygen species (ROS) and hypoxia deteriorate the inflammation‐related diseases such as myocardial infarction (MI), and thereby deter the normal tissue repair and recovery and further lead to severe fibrosis and malfunction of tissues and organs. In particular, the MI has become one of the leading causes of death nowadays. In this study, a novel type of injectable hydrogel with dual functions of ROS scavenging and O2 generating is fabricated for MI treatment in vivo. The hydrogel is formed within 3 s from the synthetic ROS‐cleavable hyperbranched polymers and methacrylate hyaluronic acid (HA‐MA) under UV‐irradiation. Addition of biocompatible and applicable catalase in vivo enables the further transition of H2 O2, a major type of ROS, to O2 and H2 O. Results of rat MI model demonstrate that this hydrogel can significantly remove excessive ROS, inhibit cell apoptosis, increase M2/M1 macrophage ratio, promote angiogenesis, reduce infarcted area, and improve cardiac functions. With the appropriate degradation rate, simple structure and composition without cell seeding, and very excellent MI therapeutic effect, this ROS scavenging and O2 generating hydrogel has a great promise to be applied clinically. Abstract : An reactive oxygen species (ROS)‐scavenging and oxygen‐generating hydrogel is made from hyperbranched polymers containing thioketal linkage and methacrylate hyaluronic acid (HA‐MA) under UV‐irradiation, and physically loaded catalase simultaneously. This hydrogel injected to myocardial infarction significantly removes excessive ROS, inhibits cell apoptosis, increases M2/M1 macrophage ratio, promotes angiogenesis, reduces infarcted area, and improves cardiac functions in vivo.